Does the Stock Market Overreact to Corporate Earnings Information? - ZAROWIN, PAUL (Journal of Finance, 1989)
ABSTRACT This paper tests whether the stock market overreacts to extreme earnings, by examining firms' stock returns over the 36 months subsequent to extreme earnings years. While the poorest earners do outperform the best earners, the poorest earners are also significantly smaller than the best earners. When poor earners are matched with good earners of equal size, there is little evidence of differential performance. This suggests that size, and not investor overreaction to earnings, is responsible for the “overreaction” phenomenon, the tendency for prior period losers to outperform prior period winners in the subsequent period.